2014
DOI: 10.1016/j.ajo.2014.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Diplopia With Prism Improves Health-Related Quality of Life

Abstract: Purpose To report change in strabismus-specific health-related quality of life (HRQOL) following treatment with prism. Design Retrospective cross-sectional study Methods Thirty-four patients with diplopia (median age 63, range 14 to 84 years) completed the Adult Strabismus-20 questionnaire (100 to 0, best to worst HRQOL) and a diplopia questionnaire in a clinical practice before prism and in prism correction. Before prism, diplopia was “sometimes” or worse for reading and/or straight ahead distance. Prism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…Adult Strabismus‐20 (AS‐20) questionnaire (Original [n = 24], Adapted [n = 1], Chinese [n = 4], Danish [n = 1])…”
Section: Resultsmentioning
confidence: 99%
“…Adult Strabismus‐20 (AS‐20) questionnaire (Original [n = 24], Adapted [n = 1], Chinese [n = 4], Danish [n = 1])…”
Section: Resultsmentioning
confidence: 99%
“…Correction of diplopia with prism is associated with improvement in reading and general function. 15 In the study of Tamhankar et al 72% of patients reported complete or partial resolution of diplopia after prism use for restrictive strabismus. 16 If the deviation is too large to correct with prisms and stable for at least six months, extraocular muscle surgery can be performed.…”
Section: Discussionmentioning
confidence: 97%
“…The measurements of this artificially produced diplopia (vergence power) are important in diagnosis and treatment. There are few studies (28,29) evaluating the effects of non-surgical treatments for strabismus on the patient's life quality. Prism correction is a commonly used non-surgical treatment for binocular diplopia in the context of a variety of different strabismus types (30).…”
Section: Nonsurgical Treatment In Diplopiamentioning
confidence: 99%